1988
DOI: 10.1212/wnl.38.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Serum haloperidol concentration and choreiform movements in Huntington's disease

Abstract: The relationship between serum haloperidol concentration and improvement in abnormal movements was investigated in 20 adult Huntington's disease (HD) patients. Serum samples and assessments of severity of chorea were simultaneously obtained from each patient. Data were obtained prior to and at one or more doses following the initiation of haloperidol in ten patients. Serum was analyzed for haloperidol by two different methods, gas chromatographic/mass spectrometric (GC/MS) and radioreceptor (RR) assays. Steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…None of the typical neuroleptics have been found to be effective in reducing chorea in placebo-controlled trials. However, in a study of haloperidol in 10 patients, oral doses of 1.5-10.0 mg/day corresponded with at least a 30 % reduction in chorea compared with baseline [78]. The quantity and quality of these efficacy data need to be taken into account when considering the risks of using typical neuroleptics, particularly tardive dyskinesia.…”
Section: Pharmacological Treatment Optionsmentioning
confidence: 99%
“…None of the typical neuroleptics have been found to be effective in reducing chorea in placebo-controlled trials. However, in a study of haloperidol in 10 patients, oral doses of 1.5-10.0 mg/day corresponded with at least a 30 % reduction in chorea compared with baseline [78]. The quantity and quality of these efficacy data need to be taken into account when considering the risks of using typical neuroleptics, particularly tardive dyskinesia.…”
Section: Pharmacological Treatment Optionsmentioning
confidence: 99%
“…Dopamine antagonists can be successful in the treatment of choreiform movements, while the use of dopamine agonists can induce chorea in patients [48,49]. The substantia nigra pars compacta (SNc) has been postulated as a potential DBS target because of its central role in dopamine projection to the striatum [50].…”
Section: Substantia Nigramentioning
confidence: 99%
“…Haloperidol, still a widely established antipsychotic drug, was never studied in a level-I HD trial. There is evidence from three level II [7][8][9] and three level III studies [10][11][12] that it may be effective in ameliorating HD-related chorea. In detail, haloperidol (2-80 mg/d; dosage was increased until chorea was suppressed) was effective in a single-blinded (videotapes presented to blinded observer) trial of 13 patients of unclear study duration [8], but failed to reduce chorea in six patients on 15 mg/d in a double-blind, crossover comparison to lithium [13].…”
Section: A1 Conventional Dopamine-blocking Medicationsmentioning
confidence: 99%
“…However, a further single-blind, cross-over study [7] of 11 patients showed an equal efficacy of haloperidol compared to tetrabenazine with less severe adverse effects in the haloperidol group, although tardive dyskinesia complicated haloperidol therapy in three of 11 patients. Barr et al [10] found low-dose haloperidol (less that 10 mg per day) to be effective to reduce chorea in an open pilot study with little added clinical benefit on doses above 10 mg per day. Two other Level-III trials [11,12] and three case reports [14][15][16] found comparable positive results in favor of haloperidol.…”
Section: A1 Conventional Dopamine-blocking Medicationsmentioning
confidence: 99%